2015
DOI: 10.1088/0957-4484/26/45/455703
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of magnetism in sub-nanometric Ni clusters embedded in Ag

Abstract: Downsizing to the nanoscale has opened up a spectrum of new magnetic phenomena yet to be discovered. In this context, we investigate the magnetic properties of Ni clusters embedded in a metallic Ag matrix. Unlike in Ni free-standing clusters, where the magnetic moment increases towards the atomic value when decreasing the cluster size, we show, by tuning the Ni cluster size down to the sub-nanoscale, that there is a size limit below which the clusters become non-magnetic when embedded in Ag. To this end, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The magnetic moments of the embedded Ni clusters not only get quenched like clusters of other 3d transition metal atoms, [76] but the Ni cluster also becomes nonmagnetic below a critical size limit. [77] The calculated magnetic moments for the MESs of the binary NiAg clusters which possess a core-shell like structural pattern with Ni atoms at the core, also indicate similar type of variation and the NiAg binary cluster indeed becomes nonmagnetic in case of the NiAg 12 cluster which is incidentally identified here as the magic cluster for the 13 atoms sized binary NiAg clusters. Starting with total magnetic moment of 9.95 µ B of pure Ni cluster, which is in accordance with the previous results, [58] the total magnetic moments of the MESs for the NiAg alloy clusters, decrease almost monotonically with the increase of Ag-content and eventually become zero for the NiAg 12 cluster, as seen from the left top panel of Fig.…”
Section: Magnetic Propertiessupporting
confidence: 55%
“…The magnetic moments of the embedded Ni clusters not only get quenched like clusters of other 3d transition metal atoms, [76] but the Ni cluster also becomes nonmagnetic below a critical size limit. [77] The calculated magnetic moments for the MESs of the binary NiAg clusters which possess a core-shell like structural pattern with Ni atoms at the core, also indicate similar type of variation and the NiAg binary cluster indeed becomes nonmagnetic in case of the NiAg 12 cluster which is incidentally identified here as the magic cluster for the 13 atoms sized binary NiAg clusters. Starting with total magnetic moment of 9.95 µ B of pure Ni cluster, which is in accordance with the previous results, [58] the total magnetic moments of the MESs for the NiAg alloy clusters, decrease almost monotonically with the increase of Ag-content and eventually become zero for the NiAg 12 cluster, as seen from the left top panel of Fig.…”
Section: Magnetic Propertiessupporting
confidence: 55%
“…Several studies have investigated the magnetic (Kitada, 1985) and magnetoresistance properties of Ag x Ni 1− x alloys (Kubinski & Holloway, 1995) where a magnetoresistance value of ~7% was observed in gas flow condensation grown nanoparticles (Dimesso & Hahn, 1998). Furthermore, microstructural and magnetic properties of dilute nickel in silver alloys have been investigated, which revealed that clusters having fewer than six atoms have a reduced associated magnetic moment due to charge transfer between the Ni sp and d orbitals (Garcia Prieto et al, 2015). Of particular relevance to this study, the evolution of silver rich Ag x Ni 1− x films at various compositions and annealing temperatures have previously been studied (Proux et al, 1999, 2000 a , 2000 b ).…”
Section: Methodsmentioning
confidence: 99%
“…However, in the presence of generic spin-orbit couplings a more complicated relationship between spin susceptibility and the strength of the various spin-dependent interaction channels emerges 32 . It may be possible to calculate G 0 eff using ab-initio methods, similarly to e.g., the treatment of Ni clusters magnetism in Ag 33 . Alternatively, one may be able to extract G 0 eff from a Kondo lattice-like model.…”
Section: Discussionmentioning
confidence: 99%